A practical guide to the pharmacological and behavioral therapy of Narcolepsy - Franceschini, Christian; Pizza, Fabio; Cavalli, Francesca; Plazzi, Giuseppe (Neurotherapeutics, 2021)
Narcolepsy is a rare, chronic, and disabling central nervous system hypersomnia; two forms can be recognized: narcolepsy type 1 (NT1) and narcolepsy type 2 (NT2). Its etiology is still largely unknown, but studies have reported a strong association between NT1 and HLA, as well as a pathogenic association with the deficiency of cerebrospinal hypocretin-1. Thus, the most reliable pathogenic hypothesis is an autoimmune process destroying hypothalamic hypocretin-producing cells. A definitive cure for narcolepsy is not available to date, and although the research in the field is highly promising, up to now, current treatments have aimed to reduce the symptoms by means of different pharmacological approaches. Moreover, overall narcolepsy symptoms management can also benefit from non-pharmacological approaches such as cognitive behavioral therapies (CBTs) and psychosocial interventions to improve the patients' quality of life in both adult and pediatric-affected individuals as well as the well-being of their families. In this review, we summarize the available therapeutic options for narcolepsy, including the pharmacological, behavioral, and psychosocial interventions.